Analysis of cutting responses of Sialon ceramic tools in high-speed milling of FGH96 superalloys. Issue 1 (1st January 2021) - Ming, Weiwei; Huang, Xianghui; Ji, Min; Xu, Jinyang; Zou, Fan; Chen, Ming
Abstract: Powder metallurgy superalloy FGH96 is being extensively used to fabricate the hot section of the aeronautic and astronautic turbine engines owing to its superior mechanical properties maintained at high-temperature environments. However, machining such a difficult-to-cut material entails high cutting forces, excessive cutting temperatures and serious tool wear. Although Sialon ceramic tools have been successfully employed in the turning and milling processes for the Inconel 718, their application for the machining of powder metallurgy superalloys is very limited. In the current work, a series of high-speed milling trials were conducted to examine the influences of the milling parameters on the cutting response and tool wear mechanisms during the milling of FGH96 with Sialon ceramic mills under dry conditions. The milling forces and machining temperatures were studied with respect to the used process parameters. The quality of cut surfaces and wear signatures of ceramic tools were also discussed. Results indicate that the resultant cutting forces only decrease until the cutting speed exceeds 315 m/min. Furthermore, the Sialon tools seem more suitable for the rough machining of FGH96 considering the surface finish and large residual tensile stress existing on the milled surface. Finally, the adhesion wear is the primary wear mode occurring at the flank surface, while the edge chipping and flaking dominate the failure of the tool rake surface.